O teatro das sombras em "Cicatrizes do Risco/Crepúsculo das Luzes" (2001), de Cida Rodrigues - Mateus Calvis Soares (2022)
The present research focuses on the novel Cicatrizes do Risco/Crepúsculo das Luzes (2001), by Cida Rodrigues, in an attempt to observe the construction of aesthetic and narrative language and the characters who compose the work. The approaches carried out are based on a set formed by the notions of culture, identity and romance, fundamental to understanding the object in question. This hypermodern contemporary work will present a narrative formed from the mixture of textual elements, that transits between prose and poetry, adding to this narrative visual elements characteristic of the hyperspectacle culture. The notion of Shadow Theater is developed in an attempt to show that both the aesthetics and narrative, as well as the varied voices in the work, are formed from the representation of the spaces they have access to.